2022
DOI: 10.1186/s12916-022-02634-4
|View full text |Cite|
|
Sign up to set email alerts
|

Childhood diabetes mellitus and early-onset kidney diseases later in life: a nationwide population-based matched cohort study

Abstract: Background The empirical evidence remains inconclusive for an association between diabetes mellitus (DM) in children and early-onset kidney disease later in life, and little is known about the effects of DM types (i.e., type 1 diabetes [T1DM] and type 2 diabetes [T2DM]) in childhood on type-specific kidney diseases. We aimed to evaluate the association of childhood DM with overall and type-specific early-onset kidney diseases later in life. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
0
4
0
1
Order By: Relevance
“…In addition, diabetic children have an increased risk of other specific kidney diseases, including tubulo-interstitial and glomerular diseases, urolithiasis, and renal failure. The risk of developing these conditions tends to be higher in children with type 2 DM than in those with type 1-DM [32]. A consistent association has been demonstrated between increased BMI in adolescents and the development of ESRD from diabetic and nondiabetic causes.…”
Section: Impact Of Obesity On Kidney Outcomes In Childrenmentioning
confidence: 70%
See 1 more Smart Citation
“…In addition, diabetic children have an increased risk of other specific kidney diseases, including tubulo-interstitial and glomerular diseases, urolithiasis, and renal failure. The risk of developing these conditions tends to be higher in children with type 2 DM than in those with type 1-DM [32]. A consistent association has been demonstrated between increased BMI in adolescents and the development of ESRD from diabetic and nondiabetic causes.…”
Section: Impact Of Obesity On Kidney Outcomes In Childrenmentioning
confidence: 70%
“…Notably, bariatric surgery has consistently demonstrated its ability to reduce the prevalence of metabolic syndrome [31]. In a study with a median follow-up of 13 years, children with DM had a 154% increased risk of early-onset kidney disease compared with their counterparts without DM [32]. In addition, diabetic children have an increased risk of other specific kidney diseases, including tubulo-interstitial and glomerular diseases, urolithiasis, and renal failure.…”
Section: Impact Of Obesity On Kidney Outcomes In Childrenmentioning
confidence: 99%
“…В Норвегии общая частота тХБП среди детей с СД1, диагностированным в возрасте 0-5 лет и 5-9 лет, была ниже, чем в 10-14 лет [17]. По данным датского регистра СД, дети более старшего возраста с СД1, диагностированным в возрасте 6-17 лет (по сравнению с более маленькими детьми с диагностированным СД1 в возрасте 0-5 лет) и дети с большей продолжительностью СД1 (по сравнению с более короткой продолжительностью СД1) чаще имели ХБП как в целом, так и в рамках диабетической нефропатии [18]. В нашем исследовании возраст дебюта СД1 6-17 лет повышал риск достижения тХБП и трансплантации vs возраст дебюта >18 лет (ОШ=2,4; 95% ДИ 1,22-5,022; р=0,012).…”
Section: Discussionunclassified
“…Moreover, su cient evidence reveals that diabetes diagnosed during childhood often leads to a more aggressive clinical course compared to when its onset in adulthood. Individuals with youth-onset diabetes tend to exhibit lower responsiveness to current interventions, faster loss of beta-cell function, increasing insulin resistance, and rapid development of albuminuria and end-organ complications, including kidney failure [11][12][13][14]. A nationwide retrospective cohort study conducted in Israel found that both childhood-onset T1D and T2D signi cantly increase the risk of ESRD [hazard ratios 36.4 (95% CI 28.3-46.9) and 19.3 (95% CI 9.6-38.8), respectively], compared to the non-diabetic population [11].…”
Section: Introductionmentioning
confidence: 99%